PENGGUNAAN MEDIA PANJARBARU UNTUK MENINGKATKAN PEMAHAMAN KONSEP BANGUN RUANG PADA SISWA KELAS V SD - Siregar, Wanti Dahlia; Manurung, Asrar Aspia; Irvan, Irvan; Anhar, Anhar (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This classroom action research aimed to improve the conceptual understanding of three-dimensional shapes among fifth-grade students at SD Negeri 065853 Medan through the use of PANJARBARU (Three-Dimensional Net Boards) as a concrete learning medium. The study employed the Kemmis and McTaggart model, conducted over two cycles. Data collection techniques included observation and written tests (pre-test and post-test). The results indicated a significant improvement in students' conceptual understanding, with the average post-test score increasing from 71.78 in the first cycle to 81.78 in the second cycle. The percentage of students achieving the minimum mastery criterion (KKM) rose from 57% to 85%. The use of PANJARBARU effectively facilitated students’ spatial visualization skills by allowing them to construct 3D objects from 2D nets, thereby enhancing both engagement and learning outcomes.